Prevalence of glucose-6-phosphate dehydrogenase (G6PD) deficiency among the fulminant hepatitis A virus infection patients - Fardad Ejtehadi; Maryam Sadat Serpoosh; Iraj Shahramian; Ladan Aminlari; Ramin Niknam; Gholam Reza Sivandzadeh; Masoud Tahani; Amin Javadifar; Fateme Sharafi; Maryam Moini (Babol University of Medical Sciences, 2024)
Background: Hepatitis A is a widespread viral infection with significant public health implications. Assessing glucose 6-phosphate dehydrogenase (G6PD) deficiency in hepatitis A patients is essential for various reasons, including prognosis, disease severity evaluation, encephalopathy risk identification, tailored management, and advancing scientific understanding. This study aimed to investigate the prevalence and clinical implications of G6PD impairment in individuals with fulminant hepatitis A. Methods: A cross-sectional descriptive analysis was conducted, involving hospitalized patients with fulminant hepatitis A. Demographic data, prevalence rates, and clinical findings were recorded in a database. The diagnosis of hepatitis A infection was confirmed using an anti-HAV IgM antibody test, and G6PD enzyme activity was measured with a fluorescent spot assay. Results: Out of 81 patients with hepatitis A, 57 (70.4%) were males, and 24 (29.5%) were females, with an average age of 24.6 years. Dark yellow urine and anorexia were the most common clinical symptoms. Notably, 30 (37%) patients lacked G6PD. The group with G6PD deficiency showed significantly higher rates of encephalopathy and mortality (P<0.01), along with elevated bilirubin (P=0.00), abnormal coagulation parameters, and low hemoglobin levels (P=0.00). Conclusion: In light of these findings, the present study proposes the implementation of routine G6PD level assessments and the evaluation of other relevant markers in regions where hepatitis A is endemic. Furthermore, the study underscores the need for vigilant monitoring of hemolysis and encephalopathy in affected patients to optimize clinical management and reduce morbidity and mortality associated with this condition.